Knowledge-based system for air traffic flow management : timetable rescheduling and centralized flow control - Li Weigang (1994)
Future air traffic management (ATM) systems have been identified as a matter of great significance for the evolution of future air navigation systems (FANS). As one function of ATM, Air Traffic Flow Management (ATFM) provides a service complementary to Air Traffic Control (ATC). In this research, a Knowledge-Based System (KBS) has been designed to try to solve the ATFM problem. For timetable rescheduling, the system attempts to modify airlines tiemtable to smooth traffic peaks at airports during rush-hours. For centralized flow control, the system works on-line to forecast the place, time and magnitude of the congestion and to take some actions to prevent this congestion. As an Artificial Intelligence language, Prolog was chosen for developing the prototype of the Knowledge-Based ATFM System. The research gives a conceptual description of the application of KBS (specially in Prolog) in the ATFM domain. Using this system, a study of the Brazilian ATFM systemincluding the main airports of the country has been done.